APOEε4 and risk of Alzheimer’s disease – time to move forward - Lefterov, Iliya; Fitz, Nicholas F.; Lu, Yi; Koldamova, Radosveta (Frontiers in Neuroscience, 2023)
The inheritance of Apolipoprotein E4 (APOEε4) brings the highest genetic risk of Alzheimer’s disease (AD), arguably the highest genetic risk in human pathology. Since the discovery of the association, APOE protein isoforms have been at the center of tens of thousands of studies and reports. While, without a doubt, our knowledge about the normal physiological function of APOE isoforms in the brain has increased tremendously, the questions of how the inheritance of the APOEε4 allele translates into a risk of AD, and the risk is materialized, remain unanswered. Moreover, the knowledge about the risk associated with APOEε4 has not helped design a meaningful preventative or therapeutic strategy. Animal models with targeted replacement of Apoe have been generated and, thanks to the recent NIH/NIA/Alzheimer’s disease Association initiative, are now freely available to AD researchers. While helpful in many aspects, none of the available models recapitulates normal physiological transcriptional regulation of the human APOE gene cluster. Changes in epigenetic regulation of APOE alleles in animal models in response to external insults have rarely been if ever, addressed. However, these animal models provide a useful tool to handle questions and investigate protein–protein interactions with proteins expressed by other recently discovered genes and gene variants considered genetic risk factors of AD, like Triggering Receptor expressed on Myeloid cells 2 (TREM2). In this review, we discuss genetic and epigenetic regulatory mechanisms controlling and influencing APOE expression and focus on interactions of APOE and TREM2 in the context of microglia and astrocytes’ role in AD-like pathology in animal models.